Methods for functional and aesthetic rehabilitation of maxillectomy defect: a systematic review - Datarkar, Abhay; Khruomo, Aneizo; Daware, Surendra (International Journal of Research in Medical Sciences, 2024)
Maxillectomy, a surgical procedure often required for the treatment of maxillofacial tumors, results in significant anatomical and functional defects. Reconstruction of these defects poses a substantial challenge due to the complex anatomy and the need to restore both form and function. Various techniques, including obturators, free flaps, virtual surgical planning (VSP), zygomatic implant and PSI have been developed to address these challenges. Objective; This systematic review aims to evaluate the effectiveness, outcomes, and complications associated with different reconstructive techniques for maxillectomy defects. A systematic literature through electronic and manual search was conducted. A total of 8 studies met the inclusion criteria, encompassing 390 patients undergoing maxillectomy reconstruction. Free flap reconstructions also showed favorable outcomes but required longer operative times and were associated with a higher incidence of donor site morbidity. While obturators are effective for small palatal defects, larger defects benefit more from autologous free tissue transfer, achieving superior functional and aesthetic outcomes. The incorporation of VSP and computer-aided design/computer-aided manufacturing (CAD/CAM) technologies significantly enhances the precision of osseous reconstructions, leading to improved patient outcomes.